Online monitoring of fatigue damage using ultrasonic methods - Tay, Kian Yang (Nanyang Technological University, 2024)
Early detection of fatigue damage remains a persistent challenge for structures subjected to fatigue stress. A recent study introduced a method to monitor material fatigue by analyzing the energy density of diffuse ultrasonic wave signals related to fatigue cycles. The results indicate that energy density consistently decreases with the formation of cracks. Due to the sensitivity of ultrasonic waves, this method can provide early warning of fatigue damage before crack formation. However, the applicability of this method across different materials and operating conditions remains an area of significant interest. This paper designs experiments based on both the normal and corroded states of Q235 steel and verifies the correlation of ultrasonic signals at different fatigue life stages of samples in various conditions. Analysis of the ultrasonic signals using the Pearson correlation coefficient shows that a decline in fatigue life leads to a continuous decrease in the correlation coefficient between the monitored signals and the original signals, confirming the method's applicability to materials under different operating conditions.